Fade statistics in microcellular mobile radio channels with shadowing - Tjhung, T.T.; Chai, C.C. (1998 IEEE International Conference on Communications, 1998)
New expressions for the average level crossing rate (LCR) and time fade duration (TFD) of the signal envelope in microcellular mobile radio channels, characterized by Rician fading and lognormal shadowing, the so-called Rice-lognormal (RLN) channel, and by Nakagami fading and lognormal shadowing, so-called Nakagami-lognormal (RLN) channel, are presented. New LCR and TFD curves as functions of the Rice K factor, the Nakagami m factor and shadowing spread /spl sigma//sub s/ are presented and discussed. The LCR and TFD expressions for the RLN channel reduce to the published formulae for the Rayleigh-lognormal (Suzuki, 1982) channel as a special case, and for very large Rice K factor, approach those formulae obtained by Loo (1985).